The prophylactic treatment of Egyptian, Trigonella foenum - graecum L., Extract in comparison to pure diosgenin on experimentally induced non-alcoholic steatohepatitis: New targets via AMPK, RAR, and FXR pathways - Manar M. Eltamalawy; A.F. Abdel-Aziz; Tarek M. Mohamed; Naglaa F. Khedr (Elsevier, 2023)
Background: Non-alcoholic steatohepatitis (NASH) is an inflammatory liver condition that damages the liver by accumulating fat. Aim: Our study sought to explore the mechanisms involved through which fengreek, Trigonella foenum - graecum L., extract (FE) or diosgenin (DSG) exerted their hepatoprotective activity in NASH-induced rat model. Methods: FE was prepared via a Soxhlet extraction, followed by acid hydrolysis. Sixty male albino rats were randomly distributed into six groups: normal control (NC) group, NASH-control group, FE group, low DSG dose (LD-1) group, medium DSG dose (MD-5) group, and high DSG dose (HD-10) group. The influence of both FE and pure DSG on serum liver indices, lipid profile, glucose, insulin, and Homeostasis model assessment (HOMA) of insulin resistance (IR) were determined. Liver histopathology, liver gene expression of adenosine monophosphate (AMP)-activated protein kinase (AMPK), Farnesoid X receptor (FXR) and retinoic acid receptor (RAR), and protein expression of phospho-acetyl CoA carboxylase (p-ACC) were evaluated. Results: A significant amelioration was noticed in serum liver indices, lipid profile, liver histopathology, body weight gain, and p-ACC/ACC protein expression in both FE and DSG treated groups compared to the NASH untreated group. DSG-treated groups significantly (p<0.05) decreased serum glucose levels and HOMA-IR compared to the NASH untreated group. FE significantly upregulated AMPK compared to the NASH untreated group and DSG-treated groups. However, RAR downregulation and FXR overexpression of the NASH group were not normalized in treated groups. Conclusion: This study proved that FE and DSG both protected the liver against NASH. The DSG impact was dose-dependent. However, the activation of the AMPK cascade was believed to be the mechanism by which FE exerted its hepatoprotective effects.